Numerical Modelling Approaches in Analysis and Design of Underground Coal Mines: A Review - Dogra, Ankush Kumar; Kaur, Prabhjot (Journal of Advanced Research in Mechanical Engineering and Technology, 2026)
Underground coal mining has remained a prolific technique in advancement of human civilization by catering to the exponentially increasing energy demands. From time and on, underground mines have undergone different disasters leading to huge loss of life and assets. Subsidence or roof collapse in mines is one of the prime destructive hazards faced in the mines. Repetitive blasting and seismic induced vibration endure to be the main causes ofsubsidence in mines. This paper reviews the development made in the numerical methods and their reliability with respect to experimental techniques in addressing hazards encountered by underground coal mines. Preliminary focus of study has been laid upon seismicity induced subsidence in mines. Analysis based on finite element method, finite difference method and discrete element method has been appraised during the study. Furthermore, potential of coupled numerical model involving meshfree analysis technique and disturbed state concept has been highlighted in analysis of crack propagation and material heterogeneity analysis in underground coal mines that ultimately leads to subsidence in mines. DOI: https://doi.org/10.24321/2455.3190.202502